Extended Producer Responsibility and Circular Economy: Three Design Flaws (Ökologisches Wirtschaften - Fachzeitschrift, 2022)
The existing system of Extended Producer Responsibility focuses on waste generation on the national level. To account for the international trade of waste and second-hand products the concept of Ultimate Producer Responsibility is a promising approach.